PERAN INTENTION TO USE DALAM MENINGKATKAN LOYALITAS PENGGUNAAN FINANCIAL TECHNOLOGI PADA GENERASI XYZ DI INDONESIA - Rizki Sri Lasmini; Astra Prima Budiarti; Awisal Fasyni; Yolandafitri Zulvia (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
Currently, there is a significant increase in users of financial technology. Financial technology is applied to payment systems and banking transactions. This research focuses on financial technology that is used in the payment system. The public's need for financial technology in the payment system has increased since the Covid-19 pandemic. Along with restrictions on community activities in Indonesia, many actions must be carried out online using technology. This study examines the factors that influence the perceived usefulness of financial technology. By looking at this factor, companies can find out what factors encourage users to continue using financial technology for a long time. For example, when the Covid-19 pandemic is over, users continue to use financial technology services because they find it easy to make transactions. Besides that, companies must know the factors that encourage users to entrust their payment activities using financial technology services to increase competitive advantage. These factors include trust, data security and privacy, quality of administrative services, perceived usefulness, and intention to adopt fintech. This research is quantitative by using Structural Equation Model (SEM). Research data was obtained by distributing questionnaires. The result of this research is that perceived usefulness and intention to adopt fintech influence significantly and directly to loyalty to use fintech.